Chemical Composition of Liquid Smoke from Mangrove Leaves: Potential Aphrodisiac Effects and Implications for Coastal Ecosystem Sustainability - Ratnani Rita D.; Mulangsri Dewi A. K.; Muhyi Ahmad; Meilani Dwi; Muhaimin Wahid; Arifan Fahmi; Steven Soen; Arianti Forita D. (BIO Web of Conferences)
This study investigates the chemical composition of liquid smoke derived from mangrove leaves ( Avicenna marina) and explores the bioactive compounds with potential aphrodisiac effects, aiming to promote coastal ecosystem sustainability. Mangrove leaves were chosen due to their abundance in coastal areas and their ecological significance in maintaining ecosystem balance. The liquid smoke production process involved pyrolysis at various temperatures to determine the optimal conditions for extracting bioactive compounds. Gas Chromatography-Mass Spectrometry (GC-MS) analysis revealed that the liquid smoke dominantly consists of phenolic compounds, organic acids, and esters, potentially contributing to aphrodisiac effects. The temperature alteration from 100-200°C to 200-300°C also enhances the composition of organic acids (42.39-42.56%) and phenols (6.22-9.51%). From a sustainability perspective, utilizing mangrove leaves for liquid smoke production can aid in coastal ecosystem conservation by reducing organic waste and enhancing the economic value of mangrove-based products. This study can support the development of environmentally friendly and economically viable coastal resources, contributing to both ecosystem preservation and local economic growth.